Cape York Peninsula : a guide to Aboriginal Regional organisations throughout Cape York Peninsula. - Cape York Partnerships (Qld.) (Cairns: Cape York Partnerships, 1995)
Information on Cape York Aboriginal regional organisations; background to establishment of the organisations; outline of Cape York Partnerships Project, which is supported by the organisations; Cape York Land Council Aboriginal Corporation; Apunipima Cape York Health Council, Cape York Aboriginal Charitable Trust and Cape York Corporation Pty Ltd (as Trustee for Cape York Aboriginal Charitable Trust); Balkanu Cape York Development Corporation Pty Ltd.
Cover title.
Keywords: Balkanu Cape York Development Corporation (Qld.); Cape York Partnerships (Qld.); Cape York Land Council (Qld.); Apunipima Cape York Health Council (Qld.); Cape York Corporation (Qld.); Aboriginal Australians -- Queensland -- Cape York Peninsula -- Social conditions; Aboriginal Australians -- Queensland -- Cape York Peninsula -- Councils; Community organisations - Health and family planning; Community organisations - Economic; Community organisations - Land rights; Councils - Land Councils; Cape York Peninsula (Qld.) -- Economic conditions; Cape York Peninsula (Qld SC54, SD54, SD55)